2005
DOI: 10.1191/1365782805li139oa
|View full text |Cite
|
Sign up to set email alerts
|

Light source spectrum, brightness perception and visual performance in pedestrian environments: a review

Abstract: This review considers the impact of light source spectral power distribution (SPD) on brightness perception and visual performance in mesopic conditions, with emphasis on the comparison of metal halide (MH) and high pressure sodium (HPS) lamps. Models of mesopic vision predict that SPD is a significant variable in that at a HPS photopic luminance of 0.100 cd/m 2 , MH need only produce about 0.070 -0.075 cd/m 2 to be seen as equally bright. However, attempts to validate the predictions of these models in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 34 publications
0
30
1
4
Order By: Relevance
“…To encourage widespread use of the trade-off there is a need to determine whether it is supported by research evidence. The first stage of this process reviewed previous studies 3 . It was concluded that further evidence is required to confirm the effect of the spectral power distribution (SPD) of lamps that are used for street lighting on brightness and visual performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To encourage widespread use of the trade-off there is a need to determine whether it is supported by research evidence. The first stage of this process reviewed previous studies 3 . It was concluded that further evidence is required to confirm the effect of the spectral power distribution (SPD) of lamps that are used for street lighting on brightness and visual performance.…”
Section: Introductionmentioning
confidence: 99%
“…Fotios, Cheal & Boyce 3 reviewed previous studies of visual performance carried out under mesopic conditions. Two recent studies 6,7 suggested that SPD does not affect achromatic, foveal acuity.…”
Section: Introductionmentioning
confidence: 99%
“…Esse ambiente é considerado agradável do ponto de vista dos participantes devido à percepção visual de maior quantidade de luz existente entre esse cenário em comparação com o primeiro, o que justifica sua relação com segurança e confirma pesquisas a respeito da relação entre esses dois parâmetros (Fotios et al, 2005;Peña-García et al, 2015).…”
Section: Análise E Discussão Dos Resultadosunclassified
“…De um lado, temos o avanço das tecnologias de iluminação e os estudos relacionados a qualidades técnicas e quantitativas, como medições fotométricas, temperatura da cor, custo, benefício e eficiência para a compreensão da influência da iluminação na performance do usuário (Knight, 2010;Fotios et al, 2005). Incluem-se ainda estudos nos quais usuários expostos a fontes luminosas são avaliados a fim de descobrir a quantidade de luz necessária para fornecer segurança física (detecção de obstáculos e reconhecimento facial) e conforto visual, além de outros aspectos, como depreciação de fontes luminosas, entre outros (Boyce et al, 2000).…”
Section: Aspectos Subjetivos Em Iluminaçãounclassified
“…1 Experimental work has been carried out to fill this gap. 2,3 Three different techniques were used for comparing the brightness of lighting from different types of light source:…”
Section: Introductionmentioning
confidence: 99%